MASSAGE EFFLURAGE USING RED GINGER EFFECTIVELY RELIEVES GOUT ARTHRITIS PAIN IN ELDERS - Hartin Suidah; Ninik Murtiyani; Reni Ayu Mita Sari (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
ABSTRACT BACKGROUND: Most elders with gout arthritis pain choose analgesic to deal with their pain. Massage efflurage using red ginger is a therapy to reduce gout arthritis pain. The objective of research was to find out the effectiveness of message efflurage using red ginger in relieving gout arthritis pain in elders. METHOD: The research design employed in this study was pre-experimental one group pre-posttest design. Independent variable was massage efflurage using red ginger and dependent variable was gout arthritis pain in elders. The population of research was all elders in Kedungbendo Village of Mojokerto Regency, consisted of 36 elders. The sample of research consisted of 33 elders taken using probability simple random sampling technique used. Pretest-posttest data were collected using numerical pain scale observation sheet. RESULT: The result of pretest-posttest obtained from 8 respondents with severe pain showed that their pain change into mild (5 respondents) and moderate pains (3). Out of 21 respondents, 9 respondents showed that their pain changed from moderate into no pain, 10 respondents into mild pain and 2 stable. Out of 4 respondents with mild pain, all of them showed that their pain changed into no pain. CONCLUSION: The result of Wilcoxon test showed 0.000 ≤ α= 0.05, meaning that there is an effective effect of massage efflurage using red ginger on the relief of gout arthritis pain in elders. This result indicated that massage efflurage using red ginger affected the gout arthritis pain scale in elders. Respondents are expected to reduce the consumption of analgesics and to switch to a safe alternative therapy to reduce negative effect related to aging process experienced by elders. Keywords: Gout Arthritis, Massage Efflurage, Red Ginger